1997
DOI: 10.1126/science.277.5322.60
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure of the Cytochrome bc 1 Complex from Bovine Heart Mitochondria

Abstract: On the basis of x-ray diffraction data to a resolution of 2.9 angstroms, atomic models of most protein components of the bovine cytochrome bc1 complex were built, including core 1, core 2, cytochrome b, subunit 6, subunit 7, a carboxyl-terminal fragment of cytochrome c1, and an amino-terminal fragment of the iron-sulfur protein. The positions of the four iron centers within the bc1 complex and the binding sites of the two specific respiratory inhibitors antimycin A and myxothiazol were identified. The membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

45
896
2
5

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 990 publications
(948 citation statements)
references
References 58 publications
45
896
2
5
Order By: Relevance
“…In quinol:-cytochrome c reductase the two heroes are ligated by only two transmembrane helices; each pair of histidines on the two helices are 13 14 residues apart. As a consequence, the two hemes are approximately oriented in the same plane and positioned at a fixed distance, 20 A, [5], from each other. In the diheme succinate:quinone oxidoreductases the relative position of the two hemes can be more flexible.…”
Section: Implications From the Sequence Comparisons And The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In quinol:-cytochrome c reductase the two heroes are ligated by only two transmembrane helices; each pair of histidines on the two helices are 13 14 residues apart. As a consequence, the two hemes are approximately oriented in the same plane and positioned at a fixed distance, 20 A, [5], from each other. In the diheme succinate:quinone oxidoreductases the relative position of the two hemes can be more flexible.…”
Section: Implications From the Sequence Comparisons And The Modelmentioning
confidence: 99%
“…SQR in many organisms contains cytochrome of b-type [1,2]. The function and structure of this cytochrome is poorly understood as compared to that of the cytochrome bc/bf (complex III, quinol:cytochrome c reductase) and cytochrome c oxidase (complex IV) [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a great deal of information is available concerning the effects of single, as well as compensatory pairs of point mutations on the assembly and function of Rhodobacter cyt bc 1 (Brasseur et al 1996). While the interpretation of these data has been greatly aided by the availability of the mitochondrial structures (Xia et al 1997;Iwata et al 1998;Zhang et al 1998;Hunte et al 2000;Gao et al 2003;Palsdottir et al 2003), there are also important differences due to specific insertions and deletions that are uniquely present in the bacterial or mitochondrial enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Various three dimensional structures of the mitochondrial cyt bc 1 , which have been accumulated during the last several years (Xia et al 1997;Iwata et al 1998;Zhang et al 1998;Hunte et al 2000;Gao et al 2003;Palsdottir et al 2003), have recently been supplemented by the structures of the cyt b 6 f from cyanobacteria and chloroplast (Kurisu et al 2003;Stroebel et al 2003). Crystallization of the simpler bacterial cyt bc 1 has been 6 considerably more challenging, and the crystals obtained to date are not particularly satisfactory for structure determination due to high mosaicity as well as poor and anisotropic crystalline order.…”
Section: Introductionmentioning
confidence: 99%
“…12 Napyradiomycin A1 is structurally similar to ubiquinone ( Figure 1a); therefore, it is likely that napyradiomycin A1 binds with the ubiquinone-binding site of complexes I and II through its terpenoid residue. On the other hand, although mitochondrial complex III also includes a ubiquinone-binding site, 13 napyradiomycin A1 was unable to inhibit the activity of complex III up to 20 mM. Our result that napyradiomycin A1 inhibits mitochondrial complexes I and II but not complex III is interesting, because it has been reported that the structure of ubiquinone-binding sites in complex I and complex III may be similar, but they are different from a ubiquinone-binding site in complex II.…”
mentioning
confidence: 47%